Seasonal Changes of Total Carbohydrate Contents in Three Varieties of Apple (Malus Sylvestris Miller) Stem Cuttings - Sivaci, A. (Elsevier Science BV, 2006)
Stems of apple (Malus sylvestris Miller) varieties 'Golden delicious', 'Starkrimson delicious' and 'Misket delicious' were taken at different times of the year and investigated to find out seasonal changes of their total carbohydrate concentrations. All investigated varieties exhibited seasonal differences in carbohydrate contents. Total carbohydrate contents of these varieties reached at the highest value in February but the lowest in May. For all the three varieties, soluble sugars and starch contents in stem tissues were found to be similar and also soluble sugars contents of stems to be higher than starch through all the sampling period (August-May). © 2006 Elsevier B.V. All rights reserved.
Keywords: Apple ('Golden Delicious' 'Starkrimson Delicious' and 'Misket Delicious'); Carbohydrates; Seasonal Changes